Wax Moth Control - Cameron J Jack; James D Ellis (EDIS)
The greater wax moth (Galleria mellonella Linnaeus) and lesser wax moth (Achroia grisella Fabricius) are major pests of honey bee colonies in Florida. The best defense against wax moths in living colonies is keeping colonies otherwise strong, free of diseases and pests, and queenright. Controlling wax moths in stored combs and equipment, however, can be more difficult. This 3-page fact sheet written by Cameron J. Jack and Jamie D. Ellis and published by the UF/IFAS Department of Entomology and Nematology details the steps beekeepers can take to control wax moths and keep them from ruining stored honey bee combs and equipment. https://edis.ifas.ufl.edu/aa141